Between two worlds [videorecording (DVD)] - Blatt, Edward A., 1903-1991; Garfield, John; Parker, Eleanor, 1922-2013; Greenstreet, Sydney; Vane, Sutton, 1888-1963 (Archive collection., 2010)
After a Nazi bomb raid on an English port town, a group of passengers aboard a luxury liner see their tickets are stamped for passage to heaven. And hell.